2011
DOI: 10.1080/17538947.2011.582888
|View full text |Cite
|
Sign up to set email alerts
|

A European perspective on Digital Earth

Abstract: The purpose of this paper is to contribute to the definition of a European perspective on Digital Earth (DE), identify some actions that can contribute to raise the awareness of DE in the European context and thus strengthen the European contribution to the International Society for Digital Earth (ISDE). The paper identifies opportunities and synergies with the current policy priorities in Europe (Europe 2020, Innovation Union and Digital Agenda) and highlights a number of key areas to advance the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…As the DE application gets closer to a market-ready product, potential industry should be attracted, for instance, as observers as part of the stakeholders networks. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Annoni et al, 2011). Virtual Globes have to be equipped with collaboration tools -as for example, access to environmental and geospatial toolboxes via standardized software development kits (SDKs), incubators for community generated DE applications or access to a shared market place.…”
Section: Support and Govern In Delimentioning
confidence: 99%
See 1 more Smart Citation
“…As the DE application gets closer to a market-ready product, potential industry should be attracted, for instance, as observers as part of the stakeholders networks. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Annoni et al, 2011). Virtual Globes have to be equipped with collaboration tools -as for example, access to environmental and geospatial toolboxes via standardized software development kits (SDKs), incubators for community generated DE applications or access to a shared market place.…”
Section: Support and Govern In Delimentioning
confidence: 99%
“…According (DE) applications would focus on knowledge discovery and access, mainly by navigating a Virtual Globe. However, recent paradigm shifts in respect to this vision (Annoni et al, 2011;Craglia et al, 2012b;Goodchild et al, 2012) recognize that there is more than one Virtual Globe, and users are getting more actively engaged by providing own data and observations. In this wider scenery context, we -for the moment -consider DE applications as a pool of geospatial-inside software solutions.…”
Section: Introduction To the Innovation Space -About Here]mentioning
confidence: 99%
“…It was envisioned by Gore (1998) as a multi-resolution, 3D representation of the planet allowing scientists, policy-makers, students and all societal sectors to manage georeferenced information and navigate them in space and time (Brovelli et al 2015). Though DE and virtual globes are often used as synonyms, according to Harvey (2009) Annoni et al 2011;Craglia et al 2012), thus underlining their correspondence to traditional Web browsers in searching, retrieving and organizing information, whose nature is however spatial (Jones 2007).…”
Section: Virtual Globes As the New Generation Visualization Platformsmentioning
confidence: 99%
“…It is worth noting that VGI has been recognized as a key opportunity for the development of DE (Craglia et al 2008;Annoni et al 2011) and that even OpenStreetMap has been shown to be well-positioned within DE's goals (Mooney and Corcoran 2014). Elvidge and Tuttle (2008) predict the power of virtual globes in democratizing content contributions by users.…”
Section: Virtual Globes For the Exploration Of Crowdsourced Geo-datamentioning
confidence: 99%
“…See Annoni et al (2011) for further information on the European perspective on Digital Earth that originates from INSPIRE, Řezník (2013) for a general overview on INSPIRE, or the national point of view provided by Cetl, Roic, and Roncevic (2008). Cognitive issues of such a concept are depicted in Kubíček, Šašinka, and Stachoň (2014).…”
Section: Inspire Requirements On Cataloguingmentioning
confidence: 99%